BENTUK PERUBAHAN FONOLOGIS DALAM BERKOMUNIKASI VIA WHATSAPP MAHASISWA UNIVERSITAS MUHAMMADIYAH MAKASSAR - Muliana Muliana; Aulia Adhari; Nur Afni; Rani Indriani; Nur Rahmi (20-87-2496)
Forms of Phonological Changes in Communicating Via Whatsapp Universitas Muhammadiyah Makassar Students. This study aims to describe the form of phoneme changes, addition of phonemes, and omission of phonemes for students of the Muhammadiyah University of Makassar, especially the 2017 Indonesian Language and Literature Education Study Program when communicating via WhatsApp. This research is descriptive qualitative. The results showed that the form of phonological changes that occurred included: phoneme changes (a) vowel phoneme /ai/ to /e/. (b) the phoneme /u/ becomes /o/. Error adding phonemes (a) adding phonemes /g/.(b) addition of the phoneme /t/. (c) addition of the phoneme /h/. Phoneme omission error (a) omission of phoneme /h/. (b) omission of the vowel phoneme /a/.